Protective effect of propolis from Tigzirt on epirubicin-induced cardiotoxicity and nephrotoxicity. - Sara Chaa; Mokhtaria Yasmina Boufadi; Soumia Keddari; Amina Hayat Benchaib (GarVal Editorial Ltda., 2021)
Context: Epirubicin (EPI), belonging to the anthracycline family, is one of the most effective chemo-therapeutic agents used in the treatment of a variety of solid and hematologic malignant tumors but Its anti-tumor efficacy is dose-dependent, but its clinical use is limited by the development of cardiac, hepatic and nephrotic toxicities. Aims: To evaluate the protective effect of ethyl acetate extract of propolis (EAP) native to Tigzirt on selected antioxidant status parameters and biomarkers of epirubicin-induced cardiotoxicity and nephrotoxicity in rats. Methods: Thirty male Wistar albino rats were divided into five groups. It orally dosed with (EAP) or quercetin during 15 days before being subjected to toxicity by injection (i.v) of a cumulative dose of 9 mg/kg of epirubicin to repair cardiac and renal damage. Results: Injection of epirubicin to rats induced cardiac and renal dysfunction as evidenced by a significant increase (P<0.05) in serum levels of biochemical markers (CKmb, BNP, LDH, troponin, urea, creatinine and uric acid). This toxicity thus caused lesions, necrosis, and inflammatory infiltrate in the heart and kidneys. The administration of 250 mg/kg of EAP allowed restoring these functions by lowering the level of these parameters. Thus, a balance of oxidative stress was demonstrated with a decrease of +50% in the level of malondialdehyde and nitric oxide and an increase in superoxide dismutase, catalase and glutathione peroxidase. Therefore, significant restoration was observed on organ architecture. Conclusions: These results show that propolis is rich in phenolic substances, which gave the protective and curative effects against epirubicin-induced cardiotoxicity and nephrotoxicity in Wistar rats.